Vertical impact force and loading rate on the gymnastics table vault - Penitente, G.; Sands, W. A.; McNeal, J. R. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to determine the effect of low and high intensity impact forces on the average loading rate during a forward handspring vault. Peak force, time to peak and impulse were used to characterize the impact vertical force during a vault performed by 12 female gymnasts. Reaction forces from right and left hands were measured at 500 Hz with two PASCO portable force platforms fixed to the vault table surface. Force data were split in two groups: Low intensity (LI: peak forces < 0.7 BW) and High intensity (HI: peak forces > 0.7 BW). Significant differences (p<.05) for force peak magnitude and impulse between groups were found. Statistically significant correlations between the loading rate and force peak (r = .56) and time to peak (r = -.64) were found for the LI group. The loading rate for the HI group correlated with time to peak (r = -.78).